Left-Handed and Right-Handed Fencers in the International Sports Arena: Specifics of Their Competitive Activity and Features of Identification - Shynkaruk, Oksana; Ulan, Alina; Bondar, Anna; Iakovenko, Olena; Strohanov, Serhii; Pavlenko, Iurii; Goncharenko, Ievgen; Krasnianskiy, Kyrylo (Physical Education Theory and Methodology, 2020)
Research purpose: To study the features of left-handed and right-handed fencers’ competitive activity, to justify the tendency of increasing the representation of left-handed fencers in the international sports arena and to substantiate the need to take into account the functional asymmetry of fencers in the initial stages of sports training. Material and Methods. 54 international competitions and 2,395 athletes were studied. The survey was attended by 25 coaches. The study of individual profiles of asymmetry involved 9 qualified fencers. During the research, the following methods were used: analysis of scientific and methodological literature and materials from the Internet, analysis of competition protocols and video analysis, sociological methods of research, pedagogical observation, pedagogical testing, methods of mathematical statistics. Results. Among the features of competitive activity of fencers with different leading extremities are: increase in the number of various attacks and counterattacks of the right-handed athletes and widespread use of complex and more varied technical and tactical actions, while the speed of performing techniques and actions can be reduced due to the lack of competitive practice with left-handed athletes; left-handed athletes’ widespread use of simple attacks without transference with high speed. The number of left-handed fencers from 2002-2003 to 2016-2017 sports seasons increased by 48 athletes. Today, they are between 12 and 42% in the first 50 world rankings. The largest number is in teams of Russia, Italy, the USA, and China. Of the 146 left-handed athletes, 45% (66 people) represent Russia, Italy, the USA, and China in the top ten. Cases of incorrect orientation of fencers’ training were identified. This determines the relevance of accounting for functional asymmetry at the initial stages of training. Conclusions. The features of duel between the fencers with dominant right and left extremities, tendency to increase the number of left-handed fencers in the international sports arena from 2002 to 2017 were determined. Fencers’ individual profiles of asymmetry were studied, cases of incorrect orientation of athletes’ training were identified.